Host-insect interaction in Brassica against turnip aphid (Lipaphis erysimi) - YADAV, RAJBIR; MEENA, S S; SINGH, G P; YADAV, D K (The Indian Journal of Agricultural Sciences, 2011)
The experiment was conducted during 2004–06 to study host-insect interaction in Brassica against turnip aphid (Lipaphis erysimi Kalt). Factorial analysis of variance showed that aphid population collected from taramira (Eruca sativa Miller) differed significantly in its behaviour from the other 5 populations of aphid. Other 5 populations of aphid were similar in their infestation and multiplication on all the tested species of Brassica. Eruca sativa and Sinapis alba carried significantly less number of aphids than other four species under contained conditions and has antibiosis against Lipaphis erysimi. Ethiopian mustard (Brassica carinata) and gobhi sarson (Brassica napus) showed antixenosis only